2019
DOI: 10.1111/ger.12451
|View full text |Cite|
|
Sign up to set email alerts
|

Gingivitis and plaque scores among residents of low‐income senior housing

Abstract: Objectives The purpose of this paper is to present Gingival Index (GI) and Plaque Scores (PS) of older and disabled adults living in low‐income senior housing and their association with sociodemographic, health status and oral health behaviours. Methods Participants were recruited from six low‐income senior housing residences in Connecticut. Primary outcome measures were Gingival Index (GI) and Plaque Scores (PS). Surveys assessed sociodemographic characteristic, beliefs and behaviours. Logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Mediators found significant in the individual logistic regression analyses for GI and PS were utilized in the multiple logistic regression analyses for each clinical outcome. Multiple regression analyses were conducted for both GI and PS with these specific cognitive and behavioral variables, controlling for selected moderators found to be significant predictors of GI and PS outcomes (Reisine et al, 2020). Controlling for education, income, and perceived oral health status, higher locus of control (odds ratio [OR] = 1.408; confidence interval [CI] = [0.992, 1.998], p = .055) and more brushing (OR = 1.840, CI = [1.039, 3.258], p = .036) predicted lower GI score.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediators found significant in the individual logistic regression analyses for GI and PS were utilized in the multiple logistic regression analyses for each clinical outcome. Multiple regression analyses were conducted for both GI and PS with these specific cognitive and behavioral variables, controlling for selected moderators found to be significant predictors of GI and PS outcomes (Reisine et al, 2020). Controlling for education, income, and perceived oral health status, higher locus of control (odds ratio [OR] = 1.408; confidence interval [CI] = [0.992, 1.998], p = .055) and more brushing (OR = 1.840, CI = [1.039, 3.258], p = .036) predicted lower GI score.…”
Section: Resultsmentioning
confidence: 99%
“…Data were collecting digitally, using QDS software and an Access database developed for the study. The principal investigators (PIs) identified clinically relevant cutoff points for each of the theoretical domains measured, based on the IM model, below which participants were determined to need individually tailored AMI intervention (Reisine et al, 2020; Schensul, Reisine, et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The theoretical model included 12 mediators—four behavioural indices and eight cognitive emotional variables—that constituted the basis for the intervention (Figure 1). 39,40 …”
Section: Methodsmentioning
confidence: 99%
“…The General Oral Health Assessment Index (GOHAI), a different but related construct, was used to assess discriminant or divergent construct validity 46‐48 in relation to outcomes and selected mediators. Measures are defined below and elsewhere 40,45,49 Demographics and background characteristics include age, gender, race/ethnicity, income and self‐rating of oral health (4‐point Likert scale 1‐4 with four as best); Oral Hygiene Self‐management Worries Scale (OHWSMS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation